The Clinical management of rape in Yaoundé-Cameroon: a descriptive study - FOUEDJIO, Jeanne Hortence (Ethiopian Journal of Reproductive Health, 2021)
Background: Sexual assault is a global health and legal challenge. Nowadays it does not only affect women and girls, but also men and boys of all ages. Management of rape cases is dependent on the lesions and the trauma sustained by the survivors. In Cameroon, a protocol has been developed by the state to improve on the care of sexual assault survivors. There is therefore need to evaluate the clinical management of rape in Yaoundé. Materials and Methods: This was a prospective descriptive study carried out over a period of 8 months among participants of all age groups visiting the 3 referral hospitals in Yaoundé. A questionnaire was used to collect data of participants from medical records and the data collected was entered and analyzed using SPSS version 23.0. Results: During the study period, 127 cases of rape were recorded The socio-demographic profile of survivors were mainly females (99.2%), with a mean age of 13 ± 10 years with the 10 to 15 age range been the most represented (25.2%). Vaginal penetration was common in most cases (78%). Survivors consulted at the hospital within 72 hours (54%) for rape (89%) and vaginal lesions (42.5%) were observed on clinical assessment. HIV serology and Hepatitis B were requested in 90.5% and 80.3% of cases respectively. Antibiotic was prescribed for 44.9% of survivors. Prevention of HIV infection by prescribing anti-retroviral was effective in 54% of cases. After the clinical examination, 33.9% of the victims had received emergency contraception. Psychological care was provided to majority of the victims (85%). Conclusion: Sexual assault remains a prominent fact of our society mainly affecting children. Preventing them involves raising public awareness. The clinical management of survivors of rape needs to be improved on following the standard protocol provided by the government.